Prediction and experimental confirmation of banana bract mosaic virus encoding miRNAs and their targets - Ramamoorthy Sankaranarayanan; Sankara Naynar Palani; Abhishek Kumar; Punitha Selvakumar A. S.; Jebasingh Tennyson (ExRNA)
Abstract Background Potyviridae is the largest plant infecting family under the monophyletic group Riboviria, infects many of the food, fodder and ornamental crops. Due to the higher mutation and recombination rate, potyvirids are evolving rapidly, adapting to the environmental chaos and expanding their hosts. Virus control measures are need to be updated as the economic importance of potyvirids is massive. microRNAs (miRNAs) are well known for their functional importance in eukaryotes and many viruses. Regardless of its biogenesis, whether canonical or noncanonical, microRNA centric antivirus approaches attract the researchers to the hopeful future of next-generation broad-spectrum antiviral measures. Methods In this study, we predicted and screened banana bract mosaic virus (BBrMV) encoding miRNAs by computation approaches and their targets on banana transcriptome using plant small RNA target analysis server (psRNAtarget). The target gene functions were annotated by Blast2GO. The predicted BBrMV miRNAs were experimentally screened by stem-loop RT-PCR. Results The results showed that, among the predicted BBrMV miRNAs, miRNA2 is conserved throughout BBrMV isolates and has multiple virus-specific target transcripts. In addition, primary experimental validation for the predicted miRNAs revealed that miRNA2 exists in the BBrMV infected banana leaf samples. Conclusions The existence of BBrMV miRNA2 is confirmed by stem-loop RT-PCR followed by cloning and sequencing. The presence of miRNA of Potyviridae is rarely addressed and would definitely spread the hope to understand the virus infectious cycle. Our report would also help to better understand and manipulate potyviral infections.